2022
DOI: 10.3390/ijms232012080
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics and Phylogenetic Analysis of the Chloroplast Genomes in Three Medicinal Salvia Species for Bioexploration

Abstract: To systematically determine their phylogenetic relationships and develop molecular markers for species discrimination of Salvia bowleyana, S. splendens, and S. officinalis, we sequenced their chloroplast genomes using the Illumina Hiseq 2500 platform. The chloroplast genomes length of S. bowleyana, S. splendens, and S. officinalis were 151,387 bp, 150,604 bp, and 151,163 bp, respectively. The six genes ndhB, rpl2, rpl23, rps7, rps12, and ycf2 were present in the IR regions. The chloroplast genomes of S. bowley… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…The plastid genomes of S. officinalis have been reported [ 12 , 44 , 45 ]. We also developed novel molecular markers for authenticating three Salvia species [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plastid genomes of S. officinalis have been reported [ 12 , 44 , 45 ]. We also developed novel molecular markers for authenticating three Salvia species [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…The plastid genomes of S. officinalis have been reported [ 12 , 44 , 45 ]. We also developed novel molecular markers for authenticating three Salvia species [ 45 ]. The nuclear genome of S. officinalis has also been reported, but the mitogenome of S. officinalis remains unknown, limiting our ability to understand the interaction of the three genomes in S. officinalis.…”
Section: Introductionmentioning
confidence: 99%
“…2022 ) (MW435407.1), S. officinalis (Du et al. 2022 ) (NC038165.1), Salvia prattii (MK944407.1; Unpublished), Salvia przewalskii (Du et al. 2019 ) (MK344723.1), Salvia umbratica (MT156375.1; Unpublished), Salvia yangii (Cao et al.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of 20 Indigofera plastomes revealed that rp s19, ycf 1, and ndh F demonstrated pronounced expansion or contraction, as reported in Salvia L., Amygdalus L., Iris L., Prunus L. subg. Cerasus Mill., and Asteraceae ( Du et al., 2021 ; Pascual-Diaz et al., 2021 ; Du et al., 2022 ; Feng et al., 2022a ; Li et al., 2022c ). These subtle differences in boundaries could potentially be used for species identification.…”
Section: Discussionmentioning
confidence: 99%